Prevalence and genotyping of bovine Cryptosporidium species in the Mediterranean and Central Anatolia Region of Turkey. (April 2020) - Yildirim, Alparslan; Adanir, Ramazan; Inci, Abdullah; Yukari, Bayram Ali; Duzlu, Onder; Onder, Zuhal; Ciloglu, Arif; Simsek, Emrah
Highlights: C. parvum was the dominant species in pre-weaned calves in the Mediterranean Sea and Central Anatolia Regions of Turkey. C. bovis and C. ryanae were mostly found in post-weaned calves and heifers. The IIaA13G2R1 and IIaA14G1R1 subtypes belong to the potentially zoonotic family IIa of C. parvum were characterized. Abstract: The prevalence of Cryptosporidium species in calves and heifers with relation to diarrhea from several herds was investigated in this study. Fecal samples were collected from 135 and 120 pre-weaned calves and 79 and 130 heifers raised in the Central Anatolia (CAR) and Mediterranean Regions (MR) of Turkey, respectively. A total of 86 post-weaned calves in CAR were also included in the study. For diagnostic comparison, all samples were examined by microscopic examination, SSU rRNA nested PCR and TaqMan real-time PCR for the presence of oocyst and Cryptosporidium DNA. In total, 102 (34.0 %) and 93 (37.2 %) of the examined samples from CAR and MR were found positive for Cryptosporidium DNA with both nested PCR and real-time PCR analyses, respectively with an overall prevalence of 35.5 %. The diagnostic sensitivity and specificity of microscopic examination were determined as 68.7 % and 100.0 % compared to molecular tools, respectively. RFLP and sequence analyses of the SSU rRNA from the PCR products revealed that 138 (70.8 %) out of 195 positive isolates were C. parvum further confirming the species-specific real-time PCR results. Among the remaining 57 (29.2 %) positive isolates, 30 (15.4 %) and 27 (13.8 %) were characterized as C. ryanae and C. bovis, respectively. C. parvum was the dominant species in pre-weaned calves especially with diarrhea while C. bovis and C. ryanae were mostly found in post-weaned calves and heifers. The sequence analyses of the gp 60 gene of C. parvum isolates revealed two subtypes (IIaA13G2R1, IIaA14G1R1) belonging to zoonotic family IIa, with IIaA13G2R1 being the most common in diarrheic calves.